The relationship between omega-3 and smoking habit: a cross-sectional study. Issue 1 (December 2016) - Scaglia, Nóris; Chatkin, José; Chapman, Kenneth; Ferreira, Ivone; Wagner, Mario; Selby, Peter; Allard, Johane; Zamel, Noe
Abstract Background Omega3 polyunsaturated fatty acids (PUFAs) are related to several diseases, including smoking. The aim of this study was to evaluate the relationship between omega-3 intake and tobacco smoking, taking into account the qualitative differences in dietary intake between smokers and non-smokers, the amount of the ingested PUFA and their red blood (RBC) contents. We also looked for an association between omega-3 RBC content and smoking, and also between omega3 intake and the level of nicotine dependence. Methods Using a cross-sectional study, we included 50 current smokers (group I) and 50 lifetime non-smokers (group II), aged 18–75 years. We screened them at the Toronto Western Hospital and the Centre for Addiction and Mental Health (Toronto, Canada). The subjects completed a questionnaire with demographic data, lifestyle habits and details of food intake. The PUFAs measured in the RBC membranes were alphalinolenic acid, eicosapentaenoic acid (EPA), docosapentaenoic acid and docosahexaenoic acid (DHA). In order to perform an adjusted comparison between smokers and non-smokers we used the ANCOVA model. Results After adjusting for confounding factors, non-smokers showed higher consumption of PUFAs, especially salmon: 800 g (0–7.740) than smokers 430 g (0–2.150)P < 0.001. They also had higher DHA levels compared to smokers: 4.81 % (2.79–10.21) and 4.13 % (2.33–7.73), respectively, p < 0.05. The other PUFAs showed no significant differences between the two groups. Conclusions Smokers ate less fish rich in omega3 fatty acids than non-smokers, showing and inverse and significant relationship between omega3 intake and smoking. Smokers had lower levels of DHA and EPA, a not previously reported finding. Considering that PUFAs probably interfere in smoking habit, the increase in omega-3 consumption may become a perspective in prevention or treatment of smoking. However, this inference must be evaluated through specific studies.